2020
DOI: 10.1113/ep088743
|View full text |Cite
|
Sign up to set email alerts
|

The acute effect of resistance exercise on limb blood flow

Abstract: Current evidence indicates that to achieve maximum health benefits, regular resistance exercise should be a key component of structured physical activity. Several studies have revealed that regular resistance exercise may be associated with impaired vascular function, although this finding is inconsistent. Proposed explanations for impairment include substantial increases in blood pressure and increased retrograde blood flow in active limbs promoted by resistance exercise. However, few studies have examined th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 68 publications
(102 reference statements)
0
16
0
Order By: Relevance
“…Acute, exercise induced-increases in vascular shear stress are likely the primary stimulus for training-induced improvements in VEF, as measured by FMD (44). Although both resistance (45) and interval exercise (46) elicit significant acute increases in mean and antegrade shear rates and have also been shown to elicit chronic improvements in vascular function (39,42,47,48), it is plausible that the total exercise dose, and especially the aerobic exercise, was not sufficient to improve FMD in this study. Alternatively, we explored the relationship between ACE exposure and FMD improvements in the training group with the hypothesis that ACEs may blunt exercise adaptations (Fig.…”
Section: Discussionmentioning
confidence: 84%
“…Acute, exercise induced-increases in vascular shear stress are likely the primary stimulus for training-induced improvements in VEF, as measured by FMD (44). Although both resistance (45) and interval exercise (46) elicit significant acute increases in mean and antegrade shear rates and have also been shown to elicit chronic improvements in vascular function (39,42,47,48), it is plausible that the total exercise dose, and especially the aerobic exercise, was not sufficient to improve FMD in this study. Alternatively, we explored the relationship between ACE exposure and FMD improvements in the training group with the hypothesis that ACEs may blunt exercise adaptations (Fig.…”
Section: Discussionmentioning
confidence: 84%
“…A possible explanation for these findings may be related to the physiological functions associated with these frequency bands. In fact, the myogenic band is related with the endothelial activity [ 37 , 38 ]: the endothelium forms an interface between the blood circulating in the lumen and the vessel wall, helping to control the flow of substances and fluid into and out of a tissue. The negative correlation between RPE and ∆PSD of the myogenic band could be ascribed to a modulation of substance transport in the blood stream related to the autonomic activity [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the myogenic band is related with the endothelial activity [ 37 , 38 ]: the endothelium forms an interface between the blood circulating in the lumen and the vessel wall, helping to control the flow of substances and fluid into and out of a tissue. The negative correlation between RPE and ∆PSD of the myogenic band could be ascribed to a modulation of substance transport in the blood stream related to the autonomic activity [ 38 ]. Indeed, the autonomic nervous system is considered one of the key factors modulating the behaviour of the endothelial functions [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Third, it has been reported that retrograde SR has pro‐atherogenic effects on the endothelium (Green et al., 2017), and in the study by Thomas et al. (2020), the change in retrograde SR was minimal after resistance exercise. Thus, they presumed that resistance exercises were not associated with detrimental SR profiles.…”
mentioning
confidence: 91%
“…In this regard, in this issue of Experimental Physiology Thomas and colleagues (2020) tested the acute effect of resistance exercise on the SR profile in active and inactive limbs in young adults. Thomas et al.…”
mentioning
confidence: 99%